DESIGNING THE ACWA LOGO AS VISUAL IDENTITY AND BRANDING FOR THE INTERNATIONAL ACADEMIC COLLABORATION ORGANIZATION - Aesthetika, Nur Maghfirah; Ainiyah, Indah Nurul; Ifanisari, Irma Fahriza; Ghafiansyah, Firdan Isya (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to explain the collaborative process carried out by students of the Faculty of Business, Law, and Social Sciences (FBHIS), Universitas Muhammadiyah Sidoarjo, in designing the official logo of the Association for Collaboration in Worldwide Academia (ACWA) as a representation of its visual identity and international branding strategy. Method: A descriptive qualitative approach was employed through several systematic stages, including needs analysis, brainstorming, visual exploration, iterative design refinement, and final validation with ACWA representatives. Data were collected through discussions, feedback sessions, and direct coordination with the partner institution. Results: The findings show that the final logo successfully embodies ACWA’s core values of academic collaboration, openness to knowledge, and intercultural synergy. The chosen visual elements stacked books, a bookmark icon, sans-serif typography, and a yellow black color palette effectively communicate ACWA’s academic orientation and international identity. ACWA expressed strong satisfaction with the final design, noting its alignment with the initial brief and its readiness for implementation as soon as the organization’s legal and digital infrastructures are officially launched. Novelty: The novelty of this study lies in demonstrating how visual communication theory, particularly Kress and van Leeuwen’s representational framework, can be integrated into community service activities to produce a collaboratively constructed and culturally sensitive visual identity for an emerging international academic consortium.